2015
DOI: 10.1255/ejms.1345
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Applicability of Mass Spectrometer Ion Sources Using a Polarity—Molecular Weight Scattergram with a 600-Sample In-House Chemical Library

Abstract: To provide a practical guideline for the selection of a mass spectrometer ion source, we compared the applicability of three types of ion source: direct analysis in real time (DART), electrospray ionization (ESI) and fast atom bombardment (FAB), using an in-house high-resolution mass spectrometry sample library consisting of approximately 600 compounds. The great majority of the compounds (92%), whose molecular weights (MWs) were broadly distributed between 150 and 1000, were detected using all the ion sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…A chemical library was constructed by collecting samples submitted to our contracted HRMS measurement service. 15,17,18 The library samples were gathered from June 2012 to March 2013, and 611 samples were obtained. The identities of all the compounds in the sample library were confirmed by HRMS using ESI time-of-flight mass spectrometry (a few samples were confirmed using a FAB sector mass spectrometer) with errors of <5 ppm compared with the elemental compositions declared by the clients of the HRMS measurement service.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A chemical library was constructed by collecting samples submitted to our contracted HRMS measurement service. 15,17,18 The library samples were gathered from June 2012 to March 2013, and 611 samples were obtained. The identities of all the compounds in the sample library were confirmed by HRMS using ESI time-of-flight mass spectrometry (a few samples were confirmed using a FAB sector mass spectrometer) with errors of <5 ppm compared with the elemental compositions declared by the clients of the HRMS measurement service.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we investigated the applicabilities of DART, electrospray ionization (ESI), and fast atom bombardment (FAB) using the molecular weight (MW) and the topological polar surface area (tPSA) 14 as the molecular polarity. 15 According to that study, DART gave a better sample detection rate in the mass range below MW 800, therefore DART is not suitable for heavy compounds (MW > 800). It was concluded that DART has high potential in compensating for the weak performance areas of ESI.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previously, we have used the topological polar surface area (tPSA) to report on the evaluation of the performance of mass spectrometer ion sources in terms of molecular polarity and molecular weight. 18 We have observed that tPSA can easily express molecular polarity using two-dimensional chemical structures without time-consuming quantum chemical calculations. 19 Furthermore, we found that tPSA satisfactorily expressed the polarity of the analytes in the ionization of mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%